Papaya (Carica papaya) latex- an alternative to rennet for cottage cheese preparation - Rana, Md. Shohel; Hoque, Md. Raihanul; Rahman, Md. Obaidur; Habib, Raihan; Siddiki, Mohammad Shohel Rana (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The study was conducted to standardize the desire level of papaya latex on quality of cheese prepared from cow milk. Materials and methods: Cheese sample was prepared using whole milk collected from Dairy Farm, Bangladesh Agricultural University. This experiment was conducted on five treatments from cow milk named as sample CC1: cow control; A1: 2 drops (0.06 gm); B1: 3 drops (0.10 gm); C1: 4 drops (0.14 gm); D1: 5 drops (0.16 gm) of papaya latex. All experimental cheeses were judged by a panel of judges for organoleptic evaluation using a score card. The total solids and ash content of the different types of cheese were determined by oven drying method according to AOAC. Fat per cent, protein and acidity were determined by Babcock method, procedure and titrating with N/10 sodium hydroxide solution, respectively described by Aggarwala and Sharma. Results: There was significant difference within the overall physical score of different samples except color score. Overall score of sample B1 was highest (93.67±1.53) and score of sample D1 was lowest (72.33±12.01). In case of chemical analysis, the highest protein value was 17.14±0.34% found in B1 and lowest value was 14.94±0.16% found in D1. The highest fat value of sample B1 was 23.00±1.00% and lowest value was 16.00±1.00% found in C1. Highest carbohydrate was found in A1 (9.44±2.25) and lowest in D1 (5.02±0.04). Total solids and moisture content of cheese differed significantly (P<0.01) among the sample. On the other hand, non-significant difference was found in acidity. Conclusion: Cheese from cow milk, time on curd coagulation have significant difference (P<0.01) but non-significant difference was found in yield. Highest yield was found in sample CC1 (200.00±5.00 gm/kg) and lowest yield was found in B1 (193.33±2.89 gm/kg). http://doi.org/10.5455/javar.2017.d218